2016
DOI: 10.1155/2016/8372493
|View full text |Cite
|
Sign up to set email alerts
|

Mathematical Modeling of Hidden Intimate Partner Violence in Spain: A Quantitative and Qualitative Approach

Abstract: The fact that women are abused by their male partner is something that happens worldwide in the 21st century. In numerous cases, abuse only becomes publicly known when a fatal event occurs and is beyond any possible remedy, that is, when men murder their female partner. Since 2003, 793 (September 4, 2015) women have been assassinated by their significant other or excouple in Spain. Only 7.2% of murdered women had reported their fear and previous intimate partner violence (IPV) to the police. Even when the numb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
4
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 17 publications
(28 reference statements)
0
4
0
Order By: Relevance
“…In understanding dynamical systems of real-world, it has been revealed that mathematical modeling plays a fundamental role which remains effective till date Khan, Ali, Bonyah, Okosun, Islam & Khan, [7] Khan, Ullah & Farhan, [8] Karthikeyan, Karthikeyan, Baskonus, Venkatachalam & Chu, [9] Jin, Qian, Chu & Rahman, [10]. Mathematical models have been formulated and analyzed in different disciplines including the social science (Lazarus,[11] De la Poza, Jódar, & Barreda, [12] Dominioni, Marasco&Romano, [13] Lemecha & Feyissa, [14] Delgadillo-Aleman, Ku-Carrillo, Perez-Amezcua & Chen-Charpentier, [15] Danford, Kimathi & Mirau, [16] Mamo, [17] Mamo, [18] Ossaiugbo & Okposo, [19] Okposo, Jonathan, Okposo & Ossaiugbo, [20] Fantaye &Birhanu, [21]. Mathematical models have been applied tosocial situations.…”
Section: Introductionmentioning
confidence: 99%
“…In understanding dynamical systems of real-world, it has been revealed that mathematical modeling plays a fundamental role which remains effective till date Khan, Ali, Bonyah, Okosun, Islam & Khan, [7] Khan, Ullah & Farhan, [8] Karthikeyan, Karthikeyan, Baskonus, Venkatachalam & Chu, [9] Jin, Qian, Chu & Rahman, [10]. Mathematical models have been formulated and analyzed in different disciplines including the social science (Lazarus,[11] De la Poza, Jódar, & Barreda, [12] Dominioni, Marasco&Romano, [13] Lemecha & Feyissa, [14] Delgadillo-Aleman, Ku-Carrillo, Perez-Amezcua & Chen-Charpentier, [15] Danford, Kimathi & Mirau, [16] Mamo, [17] Mamo, [18] Ossaiugbo & Okposo, [19] Okposo, Jonathan, Okposo & Ossaiugbo, [20] Fantaye &Birhanu, [21]. Mathematical models have been applied tosocial situations.…”
Section: Introductionmentioning
confidence: 99%
“…One of the phenomena that can be presented by the mathematical model is the impact and expansion of racism-corruption coexistence among the communities. In this study, we have reviewed a literature done by other scholars to examine the spread and transmission of racism and corruption single existence as infectious diseases with a mathematical modelling approach as stated in [ 8 , 9 , 12 , 15 , 18 , 21 23 , 27 , 28 , 30 , 31 , 39 45 ], some applied modeling approach for social media addiction [ 20 ], and some used modeling approach for violence [ 6 , 7 , 10 , 11 ]. However, to the best of our knowledge, no one has developed and analyzed a mathematical model on racism-corruption coexistence among individuals in a given society.…”
Section: Introductionmentioning
confidence: 99%
“…Taking the racial nickname, considering situations, and when people may be ignored by members or participants due to their clan are also racism [4,6,7]. Racism in today's society breeds horrible diseases in communities including serious dangers of lingering flaws, confounding of corporate structures, and a decline in the social coherence of present associations [8][9][10]. Violence is the acyclic act that contains an accumulation of stress and acute violence that can be the heart of racism [5,6,11].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…We search for models to describe the evolution in time of violence or related variables. With this approach, we find models such as the one reported by Poza et al [9] which is an epidemiological type model that describes the evolution of the populations of different types of men, who were classified according to their level of woman abuse in Spain. This model is in terms of difference equations and predicts the evolution of IPV in Spain based on the statistical information reported by the literature.…”
Section: Introductionmentioning
confidence: 99%